(untitled) (Research, Society and Development, 2020)
Plants’ biochemical responses to water deficit are associated with their ability to synthesize accumulate osmolytes compatible to regulatory properties of water potential. The aim of the current study is to evaluate carbon and nitrogen metabolism in Tachigali vulgaris plants subjected to three water suspension periods. The experiment was carried out in greenhouse and followed a completely randomized design, at 3 x 2 factorial arrangement (three times: zero, five and ten water suspension days; and two water conditions: control and water deficit), with 4 repetitions; results were subjected to analysis of variance and means were compared through t-test at 5% probability level, in statistical package (Assistat 7.7 beta). The following variables recorded decreased values: relative water content RWC in leaf tissue (by 32.14%); nitrate ion in leaves (by 18.67%) and in roots (by 14.40%); nitrate reductase enzyme activity in leaves (by 17.06%) and roots (by 15.77%); starch concentration in leaf tissue (by 44.98%) and roots (by 21.07%). On the other hand, the following variables recorded increased values: free ammonium concentration in leaves (by 64.83%) and roots (by 1.61%); total soluble amino acids in leaf tissue (by 28.03%) and roots (by 8.42%); total soluble carbohydrates in leaves (by 3.12%) and roots (by 11.05%); sucrose in leaves (by 4.77%) and roots (by 24.77%); proline in leaves (by 193.58%) and roots (by 57.26%). Biochemical processes observed in T. vulgaris plants were affected by water deficit, which indicated that this species is capable of adopting mechanisms and strategies in order to survive under stressful conditions.